Twenty years of Rev Rene - Maria Vera Lúcia Moreira Leitão Cardoso; Lorita Marlena Freitag Pagliuca (Universidade Federal do Ceará, 2020)
When an important date arrives, it is only natural to remember the milestones of the trajectory that led to it. Reminiscing these facts, especially when they illuminate a path full of work and commitment, brings us feelings of victory. Filled with joy and reassurance feeling a push forward, this journal has reached its twentieth year.